2000
DOI: 10.1186/cc691
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinaemia after major thoracic surgery: comparison between open-heart surgery and oesophagectomy

Abstract: Background:Hyperbilirubinaemia is a common occurrence in patients who are admitted to intensive care units (ICUs) after major surgery, and it is associated with high mortality. We investigated the incidence of hyperbilirubinaemia after two major types of thoracic surgery: open-heart surgery and oesophagectomy. In order to identify the risk factors associated with hyperbilirubinaemia after major surgery, we compared the incidence after open-heart surgery with that after oesophagectomy.Results:Hyperbilirubinaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…Postoperative hyperbilirubinemia has been reported to occur in 3–35% of cardiovascular surgery patients [1,2,3,4,5,6,7,8,9,10,11], mostly with a rate greater than 20%. In addition, the rate of incidence in patients who have undergone heart valve surgery has been reported to be even higher than in those who did not, ranging from 30–40% [6,9,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative hyperbilirubinemia has been reported to occur in 3–35% of cardiovascular surgery patients [1,2,3,4,5,6,7,8,9,10,11], mostly with a rate greater than 20%. In addition, the rate of incidence in patients who have undergone heart valve surgery has been reported to be even higher than in those who did not, ranging from 30–40% [6,9,13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in surgical techniques and perioperative management, the incidence of postoperative hyperbilirubinemia after open-heart surgery is estimated to be nearly 20% [1,2,3,4,5,6,7,8,9,10], which has been consistent since the first report in 1967 [1,2]. Previous studies have suggested a number of possible risk factors underlying the development of postoperative hyperbilirubinemia, including age, heart failure [10,11], cardiopulmonary bypass time [9,10], transfusion [6,9], hemolysis [6] and sepsis [1].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and appropriate management to prevent the aggravation of PICs might be necessary to achieve favorable long-term outcomes after highly invasive esophagectomy with LN dissection for esophageal cancer. Several studies have already reported that hyperbilirubinemia is associated with not only major thoracic surgery such as esophagectomy but also post-esophagectomy complications [ 11 , 12 ]. We conducted this retrospective study to elucidate the clinical significance of postoperative hyperbilirubinemia especially in the management of patients with esophageal cancer after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that surgical stress and inflammation after major surgery cause postoperative hyperbilirubinemia [ 10 ]. In addition, several studies have elucidated that postoperative hyperbilirubinemia is associated with the extent of surgery and postoperative complications [ 11 , 12 ]. However, the clinical implication of postoperative hyperbilirubinemia in the management of these patients has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Poeze and colleagues demonstrated that increased transaminases and bilirubin precede the development of organ dysfunction after elective high-risk surgery [51] and hyperbilirubinaemia was associated with a two-fold duration of ICU-stay [52] and an increased incidence of complications after esophageal resection. Moreover, inadequate hyperactivation of the APR in patients with unresectable pancreatic cancer was associated with shorter time of survival.…”
Section: Omega 3 Fa and Liver Functionmentioning
confidence: 99%